Edible films solution developed from carboxymethyl cellulose / sesame oil: Physical, mechanical and microbial attributes of films - Fatemeh Khoshdouni Farahani; Abdul Rasul Oromiehi; Anousheh Sharifan; Zahra Khoshdouni Farahani (Applied Food Research)
Strawberry is a fruit with high nutritional value with a short shelf life, and this research provides effective preservation by coating it with edible films of carboxymethyl cellulose and sesame oil. In this study, carboxymethyl cellulose edible film with percentages of 0.0, 0.2, 0.4 and 0.6 % was built from sesame oil and mechanical, physical and microbial characterizations were reviewed. The outcomes of physical and mechanical factors indicated that the tensile strength (8.93 MPa) and elastic modulus in the coating of 0.2 % oil was lower than the control and an increase in the strain at the breaking point (51.73 %) was seen. In water vapor permeability of emulsion films, oil concentration did not make a significant difference (P > 0.05). Microbial agent test results also indicated that edible antimicrobial coatings with 0.2 % sesame oil along with potassium sorbate could create a suitable inhibitory impact on fresh strawberry fruit (0.93 × 103 CFU/gram). This biofilm could extend the shelf life of products with improved formulations and could be combined with other bioactive compounds to add nutritional value.